Apathy in Learning after Pandemic COVID-19: Students’ Experiences and Perceptions - Rijal, Dipendra (Studies in ELT and Applied Linguistics, 2025)
Apathy has become a burning issue in the present academia. Covid 19 pandemic has disrupted the educational landscape and triggered apathy among students. The current study delved into the causes of apathy and explored the experiences and perceptions of apathetic students in learning after the Pandemic Covid-19 through phenomenological research design. The students who were studying English education at Nilkantha Multiple Campus, Dhading in Bachelor level with apathetic feelings such as lack of interest, low self-efficacy, demotivation, disengagement and frustration towards learning after COVID-19 were selected through purposive sampling procedures. Their perceptions were obtained through in-depth interviews and focused group discussion (FGD). I generated several codes from the verbatim obtained from four respondents and drew themes and sub-themes from them. The respondents shared various sources of apathy categorized into three areas: external, personal, pedagogical factors for promoting apathy in students that contribute for the systematic analysis and discussion of the data. The findings unveiled that the impact of COVID-19 pandemic, peer influence, low self-efficacy and self-determination, traumatic feelings, personality traits, conventional practices, lacking conducive academic culture were the major sources of student apathy. The participants expressed their desires to have proper academic culture, student-friendly practices and treatments from teachers, inspirational and students counseling programmes in college to overcome their apathy that support the creation of a conducive environment of learning.